A CONCEPTUAL PAPER ON ALIGNING ENGLISH LANGUAGE TEACHING WITH INDUSTRY NEEDS IN TECHNOLOGICAL INSTITUTES - Bukhari, Mahin; Patoliya , Virali (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper delves into the critical alignment of English Language Teaching (ELT) with the evolving demands of industry, specifically within the context of technological institutes. By adopting innovative approaches, it emphasizes the pivotal role of English for Specific Purposes (ESP) in preparing students for the complexities of workplace communication. Central to this exploration are strategies such as detailed needs analysis, genre-based instruction, and the integration of essential workplace- relevant communication skills. Drawing extensively on insights from leading research, the paper identifies significant gaps between the outcomes of traditional academic language learning and the practical communication requirements of the modern workplace. To address this, the paper proposes dynamic curriculum innovations tailored to the specific needs of technology-driven industries. The proposed framework integrates authentic materials to simulate real-world contexts, fosters collaboration with industry experts to ensure relevance, and adopts blended learning models to combine theoretical knowledge with practical application. This comprehensive approach seeks to equip graduates not only with linguistic proficiency but also with the confidence and competence to excel in their careers, making them more adaptable and competitive in technology-focused fields.